Scheduled endoscopic surveillance controls secondary cancer after curative endoscopic resection for early gastric cancer: a multicentre retrospective cohort study by Osaka University ESD study group. Issue 10 (21st August 2012) - Kato, Motohiko; Nishida, Tsutomu; Yamamoto, Katsumi; Hayashi, Shiro; Kitamura, Shinji; Yabuta, Takamasa; Yoshio, Toshiyuki; Nakamura, Takeshi; Komori, Masato; Kawai, Naoki; Nishihara, Akihiro; Nakanishi, Fumihiko; et al.
Abstract : Background: After endoscopic submucosal dissection (ESD) of early gastric cancer (EGC), patients are at high risk for synchronous or metachronous multiple gastric cancers. Objective: To elucidate the time at which multiple cancers develop and to determine whether scheduled endoscopic surveillance might control their development. Design: A multicentre retrospective cohort study from 12 hospitals was conducted. Patients with EGC who underwent ESD with en bloc margin-negative curative resection were included. Synchronous cancer was classified as concomitant cancer or missed cancer. The cumulative incidence of metachronous cancers and overall survival rate were calculated using the Kaplan–Meier method. Results: From April 1999 to December 2010, 1258 patients met the inclusion criteria. Synchronous or metachronous multiple cancers were detected in 175 patients (13.9%) during a mean of 26.8 months. Among the 110 synchronous cancers, 21 were missed at the time of the initial ESD. Many of the missed lesions existed in the upper third of the stomach and the miss rate was associated with the endoscopist's inexperience (<500 oesophagogastroduodenoscopy cases). The cumulative incidence of metachronous cancers increased linearly and the mean annual incidence rate was 3.5%. The incidence rate did not differ between patients with or without Helicobacter pylori eradication. Four lesions (0.32%) were detected as massively invading cancers during the follow-up. Conclusions: Nineteen per cent of synchronous cancers were not detected until the initial ESD. The incidence rate of metachronous cancer after ESD was constant. Scheduled endoscopic surveillance showed that almost all recurrent lesions were treatable by endoscopic resection.